PENINGKATAN PENGETAHUAN KONSUMSI VITAMIN PADA MASA PANDEMI COVID-19 DI JATIASIH - Herty Nur Tanty; Yudha Sukowati; Meiana Dwi Andini (Jurnal Pengabdian IKIFA, 2021)
Supplements are one of the supporting nutrients that are popular with the public during this pandemic. One of these groups is vitamins. In the elderly, it is necessary to increase the consumption of several vitamins, such as vitamin C (200 mg – 2 g/day), vitamin E (134 – 800 mg/day), vitamin D (10 – 100 g/day). Increased consumption of vitamins needs to be balanced with public knowledge about the right way to consume vitamins, in order to obtain effective results on health. Errors in dosage or consumption time can cause health problems for consumers. This has prompted us to carry out outreach activities to the public regarding the right way to consume vitamins during the Covid-19 pandemic. Statistical tests show that there is an effect of providing counseling with increasing public knowledge about how to consume good vitamins. The highest increase in knowledge was in question number 3 regarding the benefits of sunbathing every morning, with an increase of 50%.